1993
DOI: 10.2134/agronj1993.00021962008500030029x
|View full text |Cite
|
Sign up to set email alerts
|

Light Transmittance, Soil Temperature, and Soil Moisture under Residue of Hairy Vetch and Rye

Abstract: Cover crop residue on the surface of soils in no-tillage systems can suppress weed emergence and growth. Although allelopathy often is invoked to explain weed suppression by residue, physical alterations of the seed environment could be important as well. This experiment was conducted to determine the light, temperature, and moisture con· ditions under cover crop residue. Hairy vetch (Yicia vil/osa Roth) and rye (Seca/e cerea/e L.) were desiccated with a contact herbicide and residue rates ranging from one-fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
377
5
21

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 445 publications
(421 citation statements)
references
References 0 publications
18
377
5
21
Order By: Relevance
“…Many Other species, mostly Anchusa italica, Sonchus oleraceus, Glycyrrhiza aspera, Xanthium strumarium, Convolvulus arvensis. studies have reported lower dry weights of weeds in systems that use cover crops because covering the inter-row spaces suppresses weed emergence (Teasdale & Mohler 1993). In the present study, weed infestation levels generally decreased as the densities of both the cover crop and maize were increased (Tables 2 and 3).…”
Section: Weed Biomasssupporting
confidence: 57%
“…Many Other species, mostly Anchusa italica, Sonchus oleraceus, Glycyrrhiza aspera, Xanthium strumarium, Convolvulus arvensis. studies have reported lower dry weights of weeds in systems that use cover crops because covering the inter-row spaces suppresses weed emergence (Teasdale & Mohler 1993). In the present study, weed infestation levels generally decreased as the densities of both the cover crop and maize were increased (Tables 2 and 3).…”
Section: Weed Biomasssupporting
confidence: 57%
“…Essa supressão ocorre durante a fase de desenvolvimento vegetativo das plantas envolvidas, e as interações são principalmente pela competição pelos recursos do ambiente e pela liberação de substâncias alelopáticas que afetam o crescimento das plantas daninhas (Teasdale & Mohler, 1993).…”
Section: Resultsunclassified
“…O milho também apresenta potencial de redução de emergência de plantas daninhas, principalmente gramíneas; para cada tonelada de palha houve redução de 6,4 e 4,2% da emergência de plantas daninhas, respectivamente, aos 26 e 41 dias após a semeadura de milho (Oliveira et al, 2001) Os efeitos da palhada sobre as plantas daninhas provêm de efeitos físicos ou alelopáticos, sendo difícil diferenciar um do outro em campo, já que ambos ocorrem de forma simultânea (Maciel et al, 2003). Os efeitos físicos da palha se devem principalmente ao sombreamento do solo, à barreira física para a emergência da plântula da espécie daninha e à manutenção de temperaturas do solo mais baixas, em relação ao solo descoberto (Aase et al, 1991;Teasdale & Mohler, 1993;Vidal, 1995).…”
Section: Introductionunclassified